Evaluation of different target genes for the detection of Salmonella sp. by loop‐mediated isothermal amplification. (16th December 2020) - Kreitlow, A.; Becker, A.; Schotte, U.; Malorny, B.; Plötz, M.; Abdulmawjood, A.
Abstract: The loop‐mediated isothermal amplification (LAMP) technique was used to investigate six salmonella‐specific sequences for their suitability to serve as targets for the pathogen identification. Sequences selected for designing LAMP primers were genes invA, bcfD, phoP, siiA, gene62181533 and a region within the ttrRSBCA locus. Primers including single nucleotide polymorphisms were configured as degenerate primers. Specificity of the designed primer sets was determined by means of 46 salmonella and 32 other food‐ and waterborne bacterial reference species and strains. Primers targeting the ttrRSBCA locus showed 100 % inclusivity of target and exclusivity of other test species and strains. Other primer sets revealed deficiencies, especially regarding Salmonella enterica subsp. II–IV and Salmonella bongori . Additionally, primers targeting the siiA gene failed to detect S. enterica subsp. enterica serotypes Newport and Stanley, whereas bcfD primers did not amplify DNA of S. enterica subsp. enterica serotype Schleissheim. TtrRSBCA primers, providing short detection times and constant melting temperatures of amplification products, achieved best overall performance. Abstract : Significance and impact of the study: This study evaluates six specific target regions in the salmonella genome using the loop‐mediated isothermal amplification technique. Primers were designed targeting five regions, which had not previously been studied intensively, and the invA gene, which is frequently used in biomolecular detection of Salmonella sp. Most primer sets were not able to amplify DNA of all tested salmonella strains, revealing deficiencies in inclusivity of the corresponding target regions. These findings highlight the differing suitability of the investigated target regions to identify Salmonella sp. and underline the importance of selecting appropriate sequences for providing reliable detection methods.